Composition and Temperature Dependence of Excess Volume of Heavy Oil-Stocks Mixtures + (Gas oil or Toluene or Reformate) - N. Slaiman, Ezzat; M. Al-Qamaje, Haidar; Z. Atta, Shahad (Al-Khwarizmi Engineering Journal, 2011)
Binary mixtures of three, heavy oil-stocks was subjected to density measurements at temperatures of 30, 35 and 40 °C. and precise data was acquired on the volumetric behavior of these systems. The results are reported in terms of equations for excess specific volumes of mixtures. The heavy oil-stocks used were of good varity, namely 40 stock, 60 stock, and 150 stock. The lightest one is 40 stock with °API gravity 33.69 while 60 stock is a middle type and 150 stock is a heavy one, with °API gravity 27.74 and 23.79 respectively. Temperatures in the range of 30-40 °C have a minor effect on excess volume of heavy oil-stock binary mixture thus, insignificant expansion or shrinkage is observed by increasing the temperature this effect becomes more significant although the heavy oil-stocks is spiked with hydrocarbons like (gas oil, toluene and reformate). Blending of Heavy oil-stocks with hydrocarbons spikes (gas oil, toluene and reformate) form non-ideal mixtures, for which excess volume can be positive or negative depending on nature species. Spiking of Heavy oil-stocks with either gas oil or reformate resulted in negative excess volume. This shrinkage is greater for the lowest boiling point spike as in the case of reformate, While, the presence of methyl groups in aromatic rings results in a positive excess volume, as shown in toluene when blended with 40 stock but a negative excess volume was found when blended with 60 stock and 150 stock. The API gravity of heavy oil-stocks has an effect on excess volume when the oil-stocks spiked with hydrocarbons like (gas oil, toluene and reformate). This 40 stocks as a typical light types resulted in minimum negative excess volume of -0.47 at 30 °C, when it was spiked with the gas oil; while the spiked heavy oil-stock with kerosene shows a maximum excess volume of -15.56 at 40 °C.